The measurements and interventions of job burnout: The leading cause of turnover cases in China’s financial institutions - Jiang Mengmeng; Jakaria Dasan (Faculty of Business, Economics and Accountancy, 2021)
Job burnout has been coined as the main cause of turnover cases. Financial institutions in China were not excluded from reporting high case of turnover due to job burnout. Studies based on literature review were carried out. These sources of review were coming from some local studies as well as from abroad. Results show that influence of individuals by job burnout and external working environment are among the factors influencing employees’ feeling of uneasiness and dissatisfaction leading to job burnout. Unless job burnout is mitigated, China’s financial institutions will keep on facing the shortfall of respective talents.